Socio-hydrology and sustainable tank management: empirical case from a Mailam tank cascade, Tamil Nadu, India - Rengalakshmi, Raj; Thamizoli, Perumal; Nagarajan, Rajendiren; Nandeesa, Pasuvanna (Frontiers in Water, 2025)
IntroductionThe tank cascade system is an interconnected tank/pond managed with local norms and social capital governed by informal institutions. These linkages closely connect people, water, and the environment in the interface of resource management for livelihoods and ecosystem services. However, in the recent past, these cascading structures have been disrupted at the hydrological and social levels, leading to complex issues with increasing climate risks and farmers’ vulnerabilities.MethodsAn in-depth study was carried out in a tank cascade system covering 14 tanks in a geographical area of 4,437 ha in South India to understand its impacts on local livelihoods, ecology, and social networks. The study adopted a mix of qualitative and quantitative methods and remote sensing data to understand the drivers of tank performance, local livelihoods, agricultural production, land use, rainfall, and interconnectedness, with a study period from 2004 to 2024.ResultsThe study analysed hydrological, social, and economic dimensions and their interconnected human-environmental interactions. The dependence on tanks for irrigation by farmers in the study area has decreased, ranging from 9 to 54%. There has been a significant change in land use; a 44% reduction in the area under cropping (1,707 ha to 954 ha), with a 13% increase in fallow land (1,607 ha to 1,822 ha) and a 43% increase in other vegetation and built-up area from 5 ha to 60 ha. The surface runoff has increased from 2029 to 2,489 ha-m, while the groundwater level shows a decreasing trend of 0.03 m below ground level (bgl) at pre-monsoon and 0.73 m bgl at the post-monsoon period, with an increase in well intensity in the ayacut area (the entire extent of land irrigated by the tank). The tank infrastructures are undergoing severe degradation, with a shift from community-based collective surface water irrigation to groundwater-based individual irrigation. The social capital and interconnectedness among the farmers are changing along with the declining relevance of community-based water governance and management systems.DiscussionIn the context of changing functional use of tanks from irrigation to groundwater recharge, tank cascade system-based infrastructure, knowledge, and its ecosystem services are on the verge of disappearance. The hydrological status of the tank cascades is closely interconnected with good governance and strategies for the sustainability of institutions in social and financial dimensions. This requires both the right policy and a translational framework to put tank cascades at the centre of the tank development plans.ConclusionIn the context of increasing climate risks and changing agrarian relations coupled with degrading ecosystem services expected from the tank landscapes, this paper delves into the importance of understanding the socio-hydrological principles in designing sustainable tank management initiatives.